2018
DOI: 10.2174/1874325001812010469
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Variables are Predictive for Patient Survival after Surgery for Skeletal Metastasis. A Prediction Model Development and External Validation Study

Abstract: Background: Predicting survival for patients with metastatic bone disease in the extremities (MBDex) is important for ensuring the implant will outlive the patient. Hitherto, prediction models for these patients have been constructed using subjective assessments, mostly lacking biochemical variables. Objectives: To develop a prediction model for survival after surgery due to MBDex using biochemical variables and exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Owing to the variety and heterogeneity of bone sarcomas, management is based on individual decision-making. While several prediction models for short-term survival have been developed for patients with metastatic bone disease 8,26 and soft tissue tumors, 9 only separate prognostic factors for survival have been identified for patients with bone sarcoma. 1,27 The decision to perform surgery and which surgical intervention to choose often relies on estimated survival based on the presence of the prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the variety and heterogeneity of bone sarcomas, management is based on individual decision-making. While several prediction models for short-term survival have been developed for patients with metastatic bone disease 8,26 and soft tissue tumors, 9 only separate prognostic factors for survival have been identified for patients with bone sarcoma. 1,27 The decision to perform surgery and which surgical intervention to choose often relies on estimated survival based on the presence of the prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to strengthen the model and circumvent observational bias, the use of objective variables, such as biochemical markers, should be considered. Several biochemical markers have proven well suited as features for prediction models in patients with bone metastasis; 26 serum lactate dehydrogenase and molecular markers, such as p-53 and p-glycoprotein, have been reported to have prognostic value for patients with osteosarcoma. 39 Thorn et al 40 found a positive correlation between high YKL-40 protein expression in tumor tissue and longer overall survival in osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%